Russia, EU enlargement and the euro - Zbigniew Polanski; Adalbert Winkler (European Central Bank (ECB), 2008)
This paper reviews selected aspects of economic relations between the EU and Russia, focusing on the impact that the last two waves of EU enlargement have had on Russia, as well as the role of the euro in Russia. The analysis suggests that if EU enlargement has had any diversion effects on trade between the EU and Russia at all, they have been minimal, while robust growth in both the EU and Russia, as well as high oil and gas prices, has boosted trade. Likewise, FDI to and from Russia has increased, with the direct impact of enlargement again difficult to disentangle from other factors. Use of the euro by Russian residents and authorities in international transactions has increased, albeit at an uneven pace. While, in general, the US dollar remains the major foreign currency used by Russian residents, the euro has gained importance as an anchor and reserve currency in Russian exchange rate policies. This has happened in the context of an overall monetary policy strategy aiming at a gradual shift from an exchange rate-oriented monetary policy to inflation targeting.
Keywords: F14; F15; F21; F36; 330; Economic integration; trade diversion; foreign direct investment; international currencies.; Internationale Wirtschaftsbeziehungen; EU-Mitgliedschaft; Handelseffekt; Euro; Reservewährung; Auslandsinvestition; EU-Staaten; Russland